2012
DOI: 10.1111/j.1528-1167.2012.03513.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mammalian target of rapamycin reduces epileptogenesis and blood–brain barrier leakage but not microglia activation

Abstract: SUMMARYPurpose: Previous studies have shown that inhibition of the mammalian target of rapamycin (mTOR) pathway with rapamycin prevents epileptogenesis after pharmacologically induced status epilepticus (SE) in rat models of temporal lobe epilepsy. Because rapamycin is also known for its immunosuppressant properties we hypothesized that one of the mechanisms by which it exerts this effect could be via suppression of brain inflammation, a process that has been suggested to play a major role in the development a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
168
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(176 citation statements)
references
References 35 publications
7
168
0
1
Order By: Relevance
“…Despite the known association between focal MCD and intractable seizures, distinguishing the differential contributions of altered brain structure, the effects of mutations on downstream gene, and protein expression, mTOR hyperactivation to epileptogenesis has been a challenge (see Aronica and Crino 2013). Although enhanced mTOR signaling is detected in knockout mouse models of mTOR regulatory genes associated with spontaneous seizures (e.g., Tsc1, Tsc2, Pten), hyperactive mTOR signaling is also found in animal models of seizures such as kainate treatment (Zeng et al 2009;Sha et al 2012) or electrical brain stimulation (van Vliet et al 2012) in the absence of structural changes in the neocortex. Enhanced mTOR activation has been linked to mouse models of infantile spasms (see Raffo et al 2011) and seizures induced in a hypoxia model lead to enhanced expression of genesencoding components of the mTOR pathway (Theilhaber et al 2013).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistmentioning
confidence: 99%
“…Despite the known association between focal MCD and intractable seizures, distinguishing the differential contributions of altered brain structure, the effects of mutations on downstream gene, and protein expression, mTOR hyperactivation to epileptogenesis has been a challenge (see Aronica and Crino 2013). Although enhanced mTOR signaling is detected in knockout mouse models of mTOR regulatory genes associated with spontaneous seizures (e.g., Tsc1, Tsc2, Pten), hyperactive mTOR signaling is also found in animal models of seizures such as kainate treatment (Zeng et al 2009;Sha et al 2012) or electrical brain stimulation (van Vliet et al 2012) in the absence of structural changes in the neocortex. Enhanced mTOR activation has been linked to mouse models of infantile spasms (see Raffo et al 2011) and seizures induced in a hypoxia model lead to enhanced expression of genesencoding components of the mTOR pathway (Theilhaber et al 2013).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistmentioning
confidence: 99%
“…Furthermore, there is increasing interest as to whether the mTOR pathway may be involved in other types of epilepsy (other than genetic epilepsies), such as epilepsy following acquired brain injury. There is some evidence that mTOR inhibitors can inhibit existing seizures or can prevent epilepsy in some animal models of acquired epilepsy, though other studies have found negative results [65][66][67][68][69].…”
Section: Tuberous Sclerosis Complex and Epilepsymentioning
confidence: 99%
“…4,5 In TLE patients with hippocampal sclerosis the mTOR pathway is activated, 6 and accordingly, mTOR hyperactivation has been demonstrated in various animal models for TLE. [6][7][8][9][10][11][12] Although the exact mechanisms through which mTOR hyperactivation could contribute to epileptogenesis are not yet fully understood, mTOR inhibition has been studied as a potential antiepileptogenic strategy in genetic as well as in acquired rodent models of epilepsy. 13 Antiepileptogenic effects of the mTOR inhibitor rapamycin have been reported in rodent post-SE models of TLE.…”
mentioning
confidence: 99%
“…13 Antiepileptogenic effects of the mTOR inhibitor rapamycin have been reported in rodent post-SE models of TLE. 7,11,12 After kainic acid (KA)-induced SE in rats, a reduction in seizure frequency and mossy fiber sprouting was observed after rapamycin treatment. 12 In the same study, it was shown that rapamycin treatment prior to SE prevented the progressive development of spontaneous seizures.…”
mentioning
confidence: 99%
See 1 more Smart Citation